2021
DOI: 10.3390/ijms221910429
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota in Lung Cancer: Where Do We Stand?

Abstract: The gut microbiota (GM) is considered to constitute a powerful “organ” capable of influencing the majority of the metabolic, nutritional, physiological, and immunological processes of the human body. To date, five microbial-mediated mechanisms have been revealed that either endorse or inhibit tumorigenesis. Although the gastrointestinal and respiratory tracts are distant physically, they have common embryonic origin and similarity in structure. The lung microbiota is far less understood, and it is suggested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 118 publications
(134 reference statements)
2
29
0
Order By: Relevance
“…Previous studies have shown that the changes of intestinal flora in patients with lung cancer are often related to Firmicutes , Bacteroides , and Proteobacteria ( Zhang et al., 2018 ; Liu et al., 2019 ; Zhuang et al., 2019 ; Zheng et al., 2020 ; Georgiou et al., 2021 ). When using the Kruskal–Wallis algorithm to further identify microbes with different abundances, it was found that the abundance of Firmicutes decreased and Proteobacteria increased in the lung cancer group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the changes of intestinal flora in patients with lung cancer are often related to Firmicutes , Bacteroides , and Proteobacteria ( Zhang et al., 2018 ; Liu et al., 2019 ; Zhuang et al., 2019 ; Zheng et al., 2020 ; Georgiou et al., 2021 ). When using the Kruskal–Wallis algorithm to further identify microbes with different abundances, it was found that the abundance of Firmicutes decreased and Proteobacteria increased in the lung cancer group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when the intestinal microbiota and its products are translocated through the epithelial barrier and then into the blood flow, they stimulate a toll-like receptor (TLR) response and the subsequent expansion of T lymphocytes into distant tissues. The translocation of bacteria from the gastrointestinal tract can enhance tumor-specific responses through TLRs or the induction of memory responses, as observed for the relationships between Enterococcus hirae and small-cell lung cancer [ 66 , 67 ].…”
Section: Microbiota In Lung Cancermentioning
confidence: 99%
“…In addition, anaerobic respiration is observed to increase in lung cancer due to the elective anaerobic qualities of the bacteria that preferentially colonize tumors. They grow in number along with cancer progression, further promoting and stabilizing the hypoxic and proinflammatory tumor environment [ 66 ]. Jin and collaborators showed that lung tumor burden was highly correlated with local bacterial abundance in the airways, but not in the intestinal tract, and deduced a relatively more significant contribution of the local microbiota in lung cancer development.…”
Section: Local Microbiota Role In Lung Cancermentioning
confidence: 99%
“…A dynamic balance exists between the host and the GM, preventing the occurrence of disease; if this balance is disturbed, many diseases will manifest (Espirito Santo et al, 2021). Research shows that the influence of the GM on its host includes immunological functions, physiological processes, material metabolism, nutritional transformation, inflammatory reactions, and cell aging (Georgiou et al, 2021). The GM has a close relationship with Parkinson's, diabetes mellitus, Alzheimer's, hypertension, non-alcoholic fatty liver disease, atherosclerosis, obesity, chronic lung disease, among others (Chen et al, 2021;Marsland et al, 2015).…”
Section: Introductionmentioning
confidence: 99%